PENGEMBANGAN TEKNIK UNTUK PEMBELAJARAN MENULIS TEKS EKSPOSISI PADA SISWA SMA KELAS X Development of Techniques for Learning to Write Exposition Texts in Tenth Grade Student - Muttaqin, Khoirul (Balai Bahasa Sumatra Barat, 2023)
This study aims to develop learning techniques for writing expository texts. The technique developed is the “PETA KONSEP” technique which is an acronym for pengalaman nyata, observasi refleksi secara individu, konseptualisasi, dan implementasi. The meaning in English is real experience, individual reflection observation, conceptualization, and implementation. The method used is the RD method, namely Four-D proposed by Thiagarajan, Semmel, and Semmel and also a few Borg Gall models. The results showed that from the validation of experts and practitioners, the method gets a value of 4.4 with very good criteria, a score of 84. Meanwhile, from users/students the method gets a value of 4.3. Furthermore, from the user implementation the method got 4.33 score. and from the user rating the method gets a value of 4.33. Thus, it can be concluded that this technique is well received by students.